Reduction in time to treatment in prehospital telemedicine evaluation and thrombolysis. (4th April 2017) - Taqui, Ather; Cerejo, Russell; Itrat, Ahmed; Briggs, Farren B.S.; Reimer, Andrew P.; Winners, Stacey; Organek, Natalie; Buletko, Andrew B.; Sheikhi, Lila; Cho, Sung-Min; Buttrick, Maureen; Donohue, Megan M.; et al.
Abstract : Objective: To compare the times to evaluation and thrombolytic treatment of patients treated with a telemedicine-enabled mobile stroke treatment unit (MSTU) vs those among patients brought to the emergency department (ED) via a traditional ambulance. Methods: We implemented a MSTU with telemedicine at our institution starting July 18, 2014. A vascular neurologist evaluated each patient via telemedicine and a neuroradiologist and vascular neurologist remotely assessed images obtained by the MSTU CT. Data were entered in a prospective registry. The evaluation and treatment of the first 100 MSTU patients (July 18, 2014–November 1, 2014) was compared to a control group of 53 patients brought to the ED via a traditional ambulance in 2014. Times were expressed as medians with their interquartile ranges. Results: Patient and stroke severity characteristics were similar between 100 MSTU and 53 ED control patients (initial NIH Stroke Scale score 6 vs 7, p = 0.679). There was a significant reduction of median alarm-to-CT scan completion times (33 minutes MSTU vs 56 minutes controls, p < 0.0001), median alarm-to-thrombolysis times (55.5 minutes MSTU vs 94 minutes controls, p < 0.0001), median door-to-thrombolysis times (31.5 minutes MSTU vs 58 minutes controls, p = 0.0012), and symptom-onset-to-thrombolysis times (97 minutes MSTU vs 122.5 minutes controls, p = 0.0485). Sixteen patients evaluated on MSTU received thrombolysis, 25% of whom received it within 60 minutes of symptom onset. Conclusion: Compared with the traditional ambulance model, telemedicine-enabled ambulance-based thrombolysis resulted in significantly decreased time to imaging and treatment.